Correlation between the severity of COVID-19 vaccine-related adverse events and the blood group of the vaccinees in Saudi Arabia: A web-based survey - Almalki, Ohoud S.; Khalifa, Amany S.; Alhemeidi, Ozouf F.; Ewis, Ashraf A.; Shady, Abeer M.; Abdelwahab, Sayed F. (Frontiers in Pharmacology, 2022)
Background: Recent epidemiological studies have reported an association between the ABO blood group and the acquisition, symptom severity, and mortality rate of coronavirus disease 2019 (COVID-19). However, the association between the ABO blood group antigens and the type and severity of COVID-19 vaccine-related adverse reactions has not been elucidated. Patients and Methods: We conducted a cross-sectional, questionnaire-based study in Saudi Arabia from February to April 2022. The study cohort included adults who had received or were willing to receive at least two doses of a COVID-19 vaccine of any type. We used Chi-square test to assess the association between the ABO blood groups and vaccine-related adverse reactions. P values of <0.05 were considered significant. Results: Of the 1180 participants, approximately half were aged 18–30 years old, 69.2% were female, and 41.6% reported their blood group as O. The most frequent COVID-19 vaccine-related adverse reactions were fatigue (65%), pain at the injection site (56%), and headache (45.9%). These adverse reactions demonstrated significant correlations with the education level (P = 0.003) and nationality (P = 0.018) of the participants following the first dose, with gender (P < 0.001) following the second dose, and with the general health status (P < 0.001) after all the doses. Remarkably, no correlation was observed between the severity of the vaccine-related adverse reactions and ABO blood groups. Conclusion: Our findings do not support a correlation between the severity of COVID-19 vaccine-related adverse reactions and the ABO blood groups of the vaccinees. The creation of a national database is necessary to account for population differences.